Estudo da diversidade de borboletas (Lepidoptera: Rhopalocera) em duas localidades no município de Frederico Westphalen, Rio Grande do Sul, Brasil - Giovenardi, Ricardo (2007)
Contributing to the butterflies diversity knowledge from Estacional Decidual Forest of Rio Grande do Sul State, a systematic survey was carried out in two localities of the Municipal District of Frederico Westphalen: Villa Faguense Municipal Park and Schöenstatt Sanctuary, from March 2005 to April 2006. In 140 hours of sampling, were registered 3129 individuals distributed in 174 species. Of the sampled species, 56,32% belong to the Nymphalidae family (12 subfamilies), 19,54% to Hesperiidae (2 subfamilies), 6,32% to Papilionidae (1 subfamily), 8,05% to Pieridae (3 subfamilies), 6,32% to Lycaenidae (2 subfamilies) and 3,45% to Riodinidae (1 subfamily). Ten species sampled were still no published for the State: Euptoieta hegesia (Cramer, 1779), Dynamine athemon (Linnaeus, 1758), Myscelia orsis (Drury, 1782), Pareuptychia summandosa (Gosse, 1880), Taygetis laches marginata (Staudinger, 1887), Yphthichoides castrensis (Schaus, 1902), Caligo eurilochus brasiliensis (Felder, 1826), Urbanus doryssus albicuspis (Herrich-Schaffer, 1869), Eurybia pergaea (Geyer, 1832), Lemonias zygia (Hübner, 1807). The Shannon-Wiener diversity index was higher in Villa Faguense Municipal Park, place less disturbed, and smaller in Schöenstatt Sanctuary. The Simpson and Berger-Parker dominance indexes had been more representative in Schöenstatt Sanctuary, with higher number of abundant species, and less representative in Villa Faguense Municipal Park. Among the species captured 131 (75.29%) are accidental, 25 (14.37%) are accessory and 18 (10.34%) are constant species.